2005
DOI: 10.1074/jbc.m406625200
|View full text |Cite
|
Sign up to set email alerts
|

Heparin II Domain of Fibronectin Uses α4β1 Integrin to Control Focal Adhesion and Stress Fiber Formation, Independent of Syndecan-4

Abstract: Co-signaling events between integrins and cell surface proteoglycans play a critical role in the organization of the cytoskeleton and adhesion forces of cells. These processes, which appear to be responsible for maintaining intraocular pressure in the human eye, involve a novel cooperative co-signaling pathway between ␣5␤1 and ␣4␤1 integrins and are independent of heparan sulfate proteoglycans. Human trabecular meshwork cells isolated from the eye were plated on type III 7-10 repeats of fibronectin (␣5␤1 ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 57 publications
2
63
0
Order By: Relevance
“…HMEC plated on the 120-kDa fragment were able to attach, however, they showed few actin stress fibers, indicating they were not completely spread. If the III 12-14 wt was added to the media, the percent of stress fiberpositive cells was enhanced 3-fold (19), whereas this increase did not occur when either mutants were added at the same concentration (P Ͻ 0.01 vs. wild type; Fig. 3D).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HMEC plated on the 120-kDa fragment were able to attach, however, they showed few actin stress fibers, indicating they were not completely spread. If the III 12-14 wt was added to the media, the percent of stress fiberpositive cells was enhanced 3-fold (19), whereas this increase did not occur when either mutants were added at the same concentration (P Ͻ 0.01 vs. wild type; Fig. 3D).…”
Section: Resultsmentioning
confidence: 99%
“…But further progression to the formation of actin stress-fibers and focal contacts requires binding of Hep-II to cell-surface proteoglycans and integrins (18)(19)(20). We therefore hypothesized that lower heparin affinity and cell binding of the III [12][13][14] W1925R and III 12-14 L1974R resulted in impaired capability to trigger stress-fiber formation and cell spreading.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are involved in focal adhesions (particularly syndecan-4), stress fiber formation (particularly syndecan-2), cytoskeletal organization and other cellular processes. (Couchman and Woods 1999;Couchman et al 2001;Santas et al 2002;Couchman 2003;Yoneda and Couchman 2003;FFilla et al 2004;Peterson et al 2005;Filla et al 2006) Syndecan-4 also appears to localize with the verticies of CLANs and syndecan-2 localizes with podosomes in the TM (Aga, et. al.…”
Section: Cell-surface Ecm Receptors Of the Tmmentioning
confidence: 99%
“…(Vittal et al 2005) This introduces two additional α4β1 integrin binding sites and has been shown to affect fibronectin's Hep II domain interactions with cells. (Santas et al 2002;Peterson et al 2005) TNF and IL-1 have modest effects and TGFβ and dexamethasone have stronger effects of the EIIIA and EIIIB splice isoforms, changing availability of integrin α9 sites (Keller et. al.…”
Section: Alternative Splicing Of Ecm Componentsmentioning
confidence: 99%